2007
DOI: 10.1089/ars.2007.1827
|View full text |Cite
|
Sign up to set email alerts
|

Capsaicin Induces Heme Oxygenase-1 Expression in HepG2 CellsViaActivation of PI3K-Nrf2 Signaling: NAD(P)H:Quinone Oxidoreductase as a Potential Target

Abstract: Capsaicin (trans-8-methyl-N-vanillyl-6-nonenamide), a major pungent ingredient of red pepper, is reported to have antimutagenic and anticarcinogenic properties. However, the mechanisms underlying its chemoprotective effects remain largely unresolved. In the present study, we found that capsaicin induced expression of heme oxygenase-1 (HO-1) in HepG2 cells. Capsaicin treatment resulted in a transient increase in the phosphorylation of Akt and subsequently nuclear translocation of NF-E2-related factor 2 (Nrf2), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
73
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 112 publications
(78 citation statements)
references
References 32 publications
5
73
0
Order By: Relevance
“…HO-1 is highly induced by oxidative stress, as well as a wide range of dietary antioxidants, such as a-lipoic acid found in broccoli and spinach, resveratrol found in grapes and isothiocyanates from brassica vegetables, according to in vitro and in vivo experiments (78)(79)(80)(81)(82). The higher exposure to exogenous antioxidants from higher intake of vegetables and fruits could increase the expression and activity of HO-1, particularly among participants who have the wild-type shorter promoters, thereby increasing its protective function in various tissues.…”
Section: Discussionmentioning
confidence: 99%
“…HO-1 is highly induced by oxidative stress, as well as a wide range of dietary antioxidants, such as a-lipoic acid found in broccoli and spinach, resveratrol found in grapes and isothiocyanates from brassica vegetables, according to in vitro and in vivo experiments (78)(79)(80)(81)(82). The higher exposure to exogenous antioxidants from higher intake of vegetables and fruits could increase the expression and activity of HO-1, particularly among participants who have the wild-type shorter promoters, thereby increasing its protective function in various tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Under the Nrf2 activation, it dissociates from Kelch-like ECHassociated protein 1 (Keap1) and translocates into the nucleus, where it binds ARE (18). Different pathways may activate Nrf2, including PI3K/Akt and MAPKs (6,13,38). We found that EP can activate Nrf2 by enhancing Nrf2 nuclear accumulation and the ARE-luciferase activity.…”
mentioning
confidence: 82%
“…Capsaicin induced apoptosis in the hepatocellular carcinoma cell line HepG2 with the involvement of intracellular Ca 2+ , ROS, Bcl-2 family, cytochrome c protein expression, and caspase-3 activity (Huang et al 2009). In the same cells, capsaicin increased ROS production and induced expression of heme oxygenase-1 (HO-1) (Lee et al 2004;Joung et al 2007). Likewise, capsaicin sensitized hepatocellular carcinoma cells as well as breast cancer cells and leukemia cells to apoptosis induced by tumor necrosis factor-related, apoptosis-inducing ligand (TRAIL) (Moon et al 2012).…”
Section: Hepatocellular Carcinomamentioning
confidence: 99%